2017
DOI: 10.18864/tjas201717
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Heavy Metals in Pseudotolithus Elongatus From Badagry Market, Nigeria

Abstract: Fish plays a significant role in food and nutrition security across the world, especially in Nigeria, where the people consume fish as a major supplement to carbohydrate-based diets. Although the fish Pseudotolithus elongatus is present in Badagry coastal waters, it is one of the popular imported fish into Nigeria and has a high price in Badagry market because of its characterized good flavor and palatability. However, there are no recent reports on the safety of consuming this fish. In this study, 182 specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
2
Order By: Relevance
“…The mean concentrations of heavy metals (except Zn) in Chrysichthys nigrodigitatus in the present study are above the limit recommended by FEPA and WHO [26]. The Fe content of C. nigrodigitatus in this study is higher than the value reported in Pseudotolithus elongatus [32]. Iron is an essential component of haemoglobin, which is responsible for oxygen transportation in the body.…”
Section: Heavy Metals In Sediment Plant and Fish Speciescontrasting
confidence: 74%
See 1 more Smart Citation
“…The mean concentrations of heavy metals (except Zn) in Chrysichthys nigrodigitatus in the present study are above the limit recommended by FEPA and WHO [26]. The Fe content of C. nigrodigitatus in this study is higher than the value reported in Pseudotolithus elongatus [32]. Iron is an essential component of haemoglobin, which is responsible for oxygen transportation in the body.…”
Section: Heavy Metals In Sediment Plant and Fish Speciescontrasting
confidence: 74%
“…The Cu content in C. nigrodigitatus recorded in this study is higher than the values reported in previous studies such as in C. nigrodigitatus [29,33] but lower than that reported in Parachanna obscura [31] from Epe Lagoon. The Zn, Pb and Cd values in fish in this study are above those found in Oreochromis niloticus [11] and in Pseudotolithus elongatus [32]. On the contrary, Pb and Cd contents recorded in C. nigrodigitatus in the present study is lower than the valus recorded in Scomber scombrus [34,35].…”
Section: Heavy Metals In Sediment Plant and Fish Speciescontrasting
confidence: 71%
“…On the contrary, the levels of Cr detected in sediment, fish and prawn for the present study did not exceed the WHO maximum limit of <25µgg -1 , 0.1µgg -1 and 0.08µgg -1 of Cr for sediment, fish and prawn respectively. Chromium is a key element in the metabolism of sugar in plants and animals and also regulate the rate played by insulin molecules in transporting glucose into the cells for glycolysis [18]. The concentration of copper (Cu) in the surface water of both Ologe Lagoon and Badagry Creek were above WHO permissible value of 0.40mgL -1 .…”
Section: Discussionmentioning
confidence: 99%